The Relationship between Discipline and Physical Work Environment on Performance with Work Motivation Mediation: Hubungan Disiplin dan Lingkungan Kerja Fisik Pada Kinerja Dengan Mediasi Motivasi Kerja - Rahayu Fajriani Rahayu; Wawan Prahiawan; Enis Khaerunnisa (Indonesian Journal of Multidisciplinary on Social and Technology, 2024)
Employee performance is the main key to the progress of a company. Adequate performance can be supported by several factors, such as discipline and work environment. The study was conducted to see how the relationship between preventive discipline and physical work environment on performance, as well as the mediation of work motivation between preventive discipline and employee performance at PT Mitra Banten Multimedia Kota Serang. A total of 92 people from the population were used as samples. SmartPLS analysis tool will be used to test the data acquisition through SEM analysis. Directly the results of the data test show that Preventive Discipline has no influence on Performance, but indirectly has an influence on Performance with the mediation of Work Motivation. An increase in Discipline and Work Motivation will lead to an increase in Employee Performance in the company. Preventive Discipline and Work Environment partially have an influence on Work Motivation and Employee Performance and Motivation has an influence on Performance at PT. Mitra Banten Multimedia Kota Serang.